2014
DOI: 10.1021/jp504293r
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Probing of the Surface Hydration of Zwitterionic Polymer Brushes: Structural and Environmental Effects

Abstract: Surface hydration has been proposed as the key nonfouling mechanism of zwitterionic materials. Because these materials have various chemical structures and will be used in complex environments, in situ probing of their surfaces in different aqueous environments is crucial to understanding their surface hydration properties. In this work, the surfaces of three zwitterionic polymer brushes in aqueous solutions with salts or varied pH were probed using sum frequency generation (SFG) vibrational spectroscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
170
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(186 citation statements)
references
References 55 publications
16
170
0
Order By: Relevance
“…These results are consistent with the sum frequency generation (SFG) vibrational spectroscopy results as reported by Leng et al, 24 i.e. sulfonbetain polymer binds divalent cations more strongly than monovalent cations.…”
Section: Surface Characterization Of Polyvbips Brushes Polyvbips Brusupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the sum frequency generation (SFG) vibrational spectroscopy results as reported by Leng et al, 24 i.e. sulfonbetain polymer binds divalent cations more strongly than monovalent cations.…”
Section: Surface Characterization Of Polyvbips Brushes Polyvbips Brusupporting
confidence: 92%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 This indicates that polyVBIPS binds K + more strongly than Na + , in agreement with previous simulation and experiment results. 24,34 . As compared to monovalent cations, MgCl 2 and CaCl 2 further decreased contact angles to ~35 ° and ~32 °, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The SFG spectroscopy was implemented according to the protocol reported previously. 33 Briefly, the visible and infrared (IR) input beams penetrated a right angle prism and overlapped spatially and temporally at the sample surface or interface. The incident angles of the visible and IR beams were 60° and 54° with respect to the surface normal, and the pulse energies of the visible and IR beams were 30 and 100 µJ, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As water comes in contact with surfaces of hydrophilic or polar materials, the structure of water at the interface differs from the bulk, and interferes with mechanical and chemical behaviors of surfaces and materials (Figure 6a). Therefore, the interfaces in exposure to water or humidity gain significant importance not only to control mechanical and chemical behavior of surface and material, but also to explore new applications [6,54,[80][81][82][83][84][85][86]. Even though understanding of this bound water layer remains incomplete, it has been shown that the changes in structure of water are dominated by hydrogen bond networks and its dynamic evolution [82,[87][88][89].…”
Section: Bound Watermentioning
confidence: 99%
“…In some hydrogels, however, bound water layer let to higher Young's moduli (stronger mechanical properties) as compared to the ones filled only with bulk water [6]. In another example, the presence of bound water on surfaces was reported to prevent fouling of materials, thus used to promote antifouling properties of surfaces [80,84]. The bound water content may be reduced in vacuum or high temperature environment and increased by exposing to water vapor, aqueous environment or humidity.…”
Section: Bound Watermentioning
confidence: 99%